Chemical Constituents and Biological Activities of Derris scandens Benth. - Deachathai, Suwanna (KKU Science Journal, 2016)
Derris scandens Benth. is well-known as an Asian medicinal plant and an important source of bioactive compounds. This review focuses on the isolated chemical structures and biological activities of the phytochemicals isolated from D. scandens from 1966-2016, according to the literature from ScienceDirect and SciFinder. Phytochemical investigation of the stems afforded a number of secondary metabolites, providing benzil derivatives, coumarins, flavones, isoflavones, isoflavone glycosides, pterocarpans, steroids, and terpenes. Sixty-six of these compounds have been reported from the plant. Twenty compounds are the new isolated compounds and three compounds are the firstly isolated from D. scandens. Several compounds have interesting pharmacological activities.